En mitad de tanto fuego by Alberto Conejero: Patroclus, protagonist of a new counter-epic - Pisano, Angelamaria (Amaltea. Journal of Myth Criticism, 2025)
This article explores the endurance of the Patroclus myth in Alberto Conejero’s play En mitad de tanto fuego. It begins by tracing the myth’s diffusion through a mythopoetic examination of its literary construction, before turning to a structural and symbolic analysis of the play’s sole character, Patroclus. By invoking collective memory, the figure of Patroclus condenses temporal opposites—past and present, beginning and end—emerging simultaneously as the assertion of a presence and the persistence of an absence. His final message is decidedly anti-war, thereby proposing a counter-epic of the soldier in love.